Solution of the equation a x ² + b x + c = 0 for b is b = ( - c - a x ² ) / x
Given,
the polynomial to be solved
a x ² + b x + c = 0
Solving the equation for b implies that we get the value of b from the above given polynomial
We can solve the given polynomial a x ² + b x + c = 0 by rearranging the terms of the polynomial and taking the LHS as b and the RHS as a term consisting of a, c and x
a x ² + b x + c = 0
=> b x = - c - a x ²
=> b = ( - c - a x ² ) / x
This gives us the required answer. It matches with option G among the given multiple choices.
Therefore, we get the solution of the equation a x ² + b x + c = 0 for b as b = ( - c - a x ² ) / x
Learn more about Polynomials here:
https://brainly.com/question/11536910?referrer=searchResults
#SPJ9